Synthesis and characterizations of amorphous carbon nanotubes/cadmium selenide quantum dots hybrid materials / Tan Kim Han - Tan, Kim Han (2012)
Carbon nanotubes (CNTs) have attracted great attention. Most of the works being conducted in the past mainly focus on the crystalline CNTs. In this work, amorphous CNTs (α-CNTs) were synthesized successfully via a simple chemical technique at 230 °C in a short period of time. Surface morphological studies revealed that the asprepared nanotubes present in straight tubular structures with open ends, having certain dimensions (80 - 110 nm for outer diameter; 45 - 65 nm for inner diameter; 8 - 10 μm for length). Both structural and elemental studies confirmed that the nanotubes were made of amorphous carbon. Acidic purification and oxidation treatment caused the surface of nanotubes rougher and introduced defects in their structures. Oxidation also increased dispersion stability of nanotubes in deionised water and ensured the successful hybridization between the α-CNTs and cadmium selenide (CdSe) quantum dots (QDs). The α-CNTs displayed π plasmon absorbance phenomenon in ultravioletvisible absorption spectra and had high band gap of 4.65 eV. The hybrid material exhibited size quantization effect due to the attachment of CdSe QDs on the nanotubes surfaces, giving the least band gap of 3 eV among the other samples. The presence of two identical bands (D and G bands) in Raman spectra deduced that both the oxidation and hybridization reduced crystallinity of the nanotubes substantially and confirmed the existence of defective walls of the nanotubes that were composed of disordered carbon. The α-CNTs exhibited lower permittivity in frequency range of 500MHz - 4.5 GHz due to quantum size effects. However, the oxidation increased the permittivity of the α- CNTs via chemical functionalization. Highest permittivity was found in the hybrid material and it was the most thermally stable sample compared to others.